Pertanggungjawaban Direksi PT. X Atas Kerugian Negara pada Pengadaan Batu dan Pasir - Angelina Tan; Lanny Kusumawati; Wafia Silvi Dhesinta Rini (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
State finances have an important role in realizing people's welfare. The parties involved in the management of state finances have obligations and responsibilities in accordance with their respective authorities which have been regulated in the laws and regulations. It should be noted that the management of BUMN and BUMD are also managers of state finances because they receive capital participation from the state. It becomes a problem when BUMD directors as BUMD financial managers cause state financial losses. The problem in question is related to accountability. This study aims to examine whether the directors of Pt. X is responsible for state financial losses that occur when he carries out his duties as a BUMD manager when carrying out the procurement of goods in the form of stones and sand. Through research conducted using the statute approach and conceptual approach, it was found that the consequences of actions in the financial management of BUMDs that are detrimental to state finances can be in the form of positional accountability and personal responsibility. Position accountability can be given if the person concerned has good intentions. However, in this case the directors of Pt. X did not have good intentions, it was found that there was an element of abuse of power which is one of the benchmarks for an act to be held personally accountable. Therefore, personal responsibility in the form of criminal sanctions and also compensation for state financial losses can be imposed on him. Keywords: state financial losses; procurement of goods; responsibility.